Lord Devlin - Sackar, John (Oxford, UK ; Hart Publishing, Bloomsbury Publishing Plc, 2020)
"Lord Devlin was a leading lawyer of his generation. Moreover, he was one of the most recognised figures in the judiciary, thanks to his role in the John Bodkin Adams trial and the Nyasaland Commission of Inquiry. It is hard then to believe that he retired as a Law Lord at a mere 58 years of age. This important book looks at the life, influences and impact of this most important judicial figure. Starting with his earliest days as a school boy before moving on to his later years, the author draws a compelling picture of a complex, brilliant man who would shape not just the law but society more generally in post-war Britain"--
Ab Ovo -- God's house -- The early years in the law -- A relentless workload -- The celebrity -- friends across the Atlantic -- Up a notch -- Darkest Africa -- The return to normality? -- Appellate life -- Not quite the wilderness -- New challenges and the enemy within -- Revenge.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Devlin, Patrick, -- Baron, -- 1905-1992.; Judges -- Great Britain -- Biography; Lawyers -- Great Britain -- Biography; Law; Electronic books